Unfinished desires : a novel - Godwin, Gail. (New York : Random House, 2009)
In the fall of 1951 at Mount St. Gabriel's, Tildy Stratton befriends Chloe Starnes, a new student. Their friendship fills a void for both girls but also sets in motion a chain of events that will profoundly affect the course of many lives.
Keywords: Catholic schools -- Fiction; Women college graduates -- Fiction; Nuns -- Fiction; Teacher-student relationships -- Fiction; Nineteen fifties -- Fiction; North Carolina -- Fiction